MODEL PENGEMBANGAN USAHA PERIKANAN YANG BERSINERGI DENGAN FUNGSI KONSERVASI KAWASAN (STATUS KASUS PENGELOLAAN SERO BERKANTONG DI PERAIRAN TELUK TIWORO, PROVINSI SULAWESI TENGGARA) - Mustaruddin, Mustaruddin (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Utilization of fisheries resources in territorial water of Tiworo Bay have tendency to destructive and pursuing only economic benefit, though the territorial water have been expressed by as area of sea conservation pursuant to SK of Head of Muna Regency No. 157 Year 2004. This research aim to knowing compatibility of sero have bag with characteristic territorial water, dynamic pattern of optimation its use, and elegibility of sero have bag effort in Tiworo Bay. Reseach method are analysis of according to (Jusuf, 1999 and Mustaruddin, 2005), analysis of dynamic systems (Muhammadi, et. al, 2001), and effort analysis (Gaspersz, 1992). Result of the research show sero have bag as compatible with environmental friendliness character of catch appliance (NK=3,4), potency of fisheries resources (NK=3,0), requirement of socialize (NK=3,3), law peripheral (NK=3,2). Optimal amount of sero have bag which can be operated dynamicly in territorial water of Tiworo Bay about 15 unit. Effort of sero have bag can conducive to clean advantage (π) which are positive, that are about Rp 70.716.800 per month. If member of fisherman sero organizer amount to 15 people, hence each people will get holder about Rp 4.714.453 per month.